Phatic Category in Oral Communication Minangkabau Language - Putri, Yessy Prima; Nelfira, Nelfira; Puspawati, Puspawati (LINGUA LITERA : journal of english linguistics and literature, 2025)
This study aims to describe the forms and functions of phatic categories in Minangkabau oral communication. Phatic categories are linguistic elements that play a role in establishing and maintaining social interactions without conveying direct informational meaning. Using a qualitative descriptive method, this research analyzes spoken data from Minangkabau speakers in Padang City, West Sumatra. The findings reveal that Minangkabau phatic expressions include bana, pun, juo, garan, ma/mah, ah, eh, a, ha, do, and lah, each serving specific social functions. For instance, bana expresses intensity, pun indicates addition/decision, eh is used by higher-status individuals toward lower-status ones, and do emphasizes denial. This study contributes to pragmatic and sociolinguistic research on regional languages, particularly in understanding the role of phatic expressions in Minangkabau society, which highly values politeness and social norms in communication.